Use the box method to distribute and simplify (x+3)(6x^2 −x). Drag and drop the terms to the correct locations of the table.left bracket

3 answers

```
x 3
+---------
6x^3 | 6x^3
-x | -x
```

Now multiply each term:

6x^3(x) = 6x^4
6x^3(3) = 18x^3
-x(x) = -x^2
-x(3) = -3x

Combine the terms:

6x^4 + 18x^3 - x^2 - 3x
the 6x^4 is supposed to be 6x^3
```
x 3
+---------
6x^2 | 6x^3
-x | -x
```

Now multiply each term:

6x^2(x) = 6x^3
6x^2(3) = 18x^2
-x(x) = -x
-x(3) = -3x

Combine the terms:

6x^3 + 18x^2 - x - 3x

Result: 6x^3 + 18x^2 - 4x